2012
DOI: 10.1016/j.jocrd.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

CBT specific process in exposure-based treatments: Initial examination in a pediatric OCD sample

Abstract: Cognitive-Behavioral theory and empirical support suggest that optimal activation of fear is a critical component for successful exposure treatment. Using this theory, we developed coding methodology for measuring CBT-specific process during exposure. We piloted this methodology in a sample of young children (N = 18) who previously received CBT as part of a randomized controlled trial. Results supported the preliminary reliability and predictive validity of coding variables with 12 week and 3 month treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…A microanalytic coding system (Exposure Process Coding System; EPCS) has been designed to measure the therapist and client behaviors outlined in this paper ( Benito, Conelea, Garcia, and Freeman, 2012 ). Pilot data from the EPCS in a small sample of young children with OCD indicate initial feasibility, reliability, and validity ( Benito, Conelea, Garcia, & Freeman, 2012 ). Furthermore, some observed therapist behaviors during exposure using the EPCS (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A microanalytic coding system (Exposure Process Coding System; EPCS) has been designed to measure the therapist and client behaviors outlined in this paper ( Benito, Conelea, Garcia, and Freeman, 2012 ). Pilot data from the EPCS in a small sample of young children with OCD indicate initial feasibility, reliability, and validity ( Benito, Conelea, Garcia, & Freeman, 2012 ). Furthermore, some observed therapist behaviors during exposure using the EPCS (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also integrate the examination of SUDS changes during ERP with the occurrence of external events (e.g., avoidance behavior) in order to construct a more complete model of exposure processes in youth. For example, Benito and colleagues (2012) reported a set of coding variables including child, therapist, and parent statements and behaviors that may be fruitful to examine in relation to distress ratings during ERP. Second, this study used multiple therapist-report measures of exposure processes, which as subjective measures are susceptible to various biases.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies with youth and adults have examined quantitative characteristics of exposure, such as the number of exposures completed per session and the amount of session time spent on conducting exposures, and findings for youth have been inconsistent. Hedtke et al (2009) found in their sample with non-OCD anxiety disorders that completing fewer exposure tasks predicted improved outcomes, whereas Benito et al (2012) found in a sample of young children with OCD that the duration of exposures was unrelated to outcomes. Thus, further research is needed regarding the association between quantitative exposure characteristics and treatment outcomes.…”
mentioning
confidence: 97%
“…The EIBS was created for the current study to assess the beliefs therapists hold regarding their own safety behaviours when delivering exposure therapy. An initial pool of 10 items was generated based on an informal review of the literature on therapist reservations about exposure therapy (Benito et al, 2012;Deacon and Farrell, 2013;Deacon et al, 2013c;Farrell et al, 2013;Harned et al, 2013;Olatunji et al, 2009), exposure therapy treatment manuals (Abramowitz et al, 2019;Barlow and Craske, 2006;Foa et al, 2012;Kendall and Hedtke, 2006), and clinical experience of the authors. Respondents rate items based on the degree to which they believe that their safety behaviours while delivering exposure therapy (as determined by the ETDS Coping Exposure subscale) are necessary for a variety of outcomes (e.g.…”
Section: Exposure Implementation Beliefs Scale (Eibs)mentioning
confidence: 99%